Factors influencing student performance in university accounting subjects - Cheng, Tan Ching (2014)
This study investigates factors that could affect the academic performance of second and third year university accounting students in Singapore. The study is important in providing guidance on the learning and teaching of accounting subjects (especially in Singapore). The sample consisted of Accountancy students of Nanyang Technological University enrolled in 1991 and 1992. The raw data was collected through use of questionnaires. A multiple regression model was employed and results indicated that Accounting background, Work experience in accounting-related field, General Paper, Additional Mathematics, Mathematics C and Absolute effort affect student performance. Implications of the findings are discussed.